Changes in T1 slope and cervical sagittal vertical axis correlate to improved neurological function recovery after cervical laminoplasty - Wang, Dong-Fan; Li, Xiang-Yu; Kong, Chao; Liu, Cheng-Xin; Shi, Bin; Lu, Shi-Bao (Frontiers in Surgery, 2022)
Purpose To investigate the influence of changes in T1 slope (T1S) and cervical sagittal vertical axis (CSVA) on cervical laminoplasty outcomes. Methods Eighty-one patients with cervical spondylotic myelopathy (CSM) treated with cervical laminoplasty were enrolled in this study. Demographic parameters included age and follow-up time. Imaging data included occiput-C2 lordosis (OC2), C2-C7 Cobb angle (CL), T1S, CSVA. Outcome assessment indicators included the Japanese Orthopedic Association (JOA) score, JOA recovery rate, and neck disability index (NDI). All patients were grouped based on preoperative T1S and variation in CL after surgery, respectively. Patients with decreased CL postoperatively were further grouped according to whether they were combined with T1S reduction. Results There were no significant differences in the final JOA score, JOA recovery rate, or NDI between patients with different T1S. Patients with loss of CL postoperatively had lower JOA score and JOA recovery rate, but higher NDI than patients with sustained CL. Furthermore, patients with CL loss but compensate for it with reduction in T1S had lower CSVA, higher JOA score and JOA recovery rate than those with CL loss alone. Conclusions Decreased T1S postoperatively prevents the tendency of the cervical spine to tilt forward by regulating CSVA and facilitates recovery of neurological function after cervical laminoplasty.